Long‐term trends in weather severity indices for dabbling ducks in eastern North America - Michael L. Schummer; John M. Coluccy; Michael Mitchell; Lena Van Den Elsen (Wildlife Society Bulletin)
ABSTRACT Annual distributions of waterfowl during the nonbreeding period can influence ecological, cultural, and economic relationships. We used previously developed Weather Severity Indices (WSI) that explained migration by dabbling ducks in eastern North America and weather data from the North American Regional Reanalysis to develop an open‐access internet‐based tool (i.e., WSI web app) to visualize and query WSI data. We used data generated by the WSI web app to determine whether the weather known to elicit southerly migration by dabbling ducks had changed, from October to April 1979 to 2013. We detected that the amount of area in the Mississippi and Atlantic Flyways with weather severe enough to cause southerly migration decreased during 1) October–December for American wigeon (Mareca americana), green‐winged teal (Anas crecca), and northern shoveler (Spatula clypeata); 2) December–January for mallard (A. platyrhynchos), American black duck (A. rubripes), and northern pintail (A. acuta); and 3) February–April for mallard, American black duck, gadwall (M. strepera), American wigeon, green‐winged teal, and northern shoveler. Results were consistent with prior research indicating that weather causing autumn and winter migration of dabbling ducks has become increasingly mild in the past 3 decades. The WSI web app enables users to query daily data and maps by species and by Flyway, Joint Venture, Landscape Conservation Cooperative, and State. We encourage those with corresponding data on participation and satisfaction by waterfowl enthusiasts (i.e., birders and hunters) to test for relationships with the WSI because of the implications for conservation funding, especially if autumn and winter weather severity continues to become increasingly mild as predicted. © 2017 The Wildlife Society.